2000
DOI: 10.1002/ir.10701
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the College‐Choice Process

Abstract: Understanding the College-Choice Process Alberto F. Cabrera, Steven M. La NasaThe literature suggests that decisions to go to college are the result of a three-stage process that begins as early as the seventh grade and ends when the high school graduate enrolls at an institution of higher education (Hossler, Braxton, and Coopersmith, 1989). In undergoing each phase of the college-choice process, high school students develop predispositions to attend college, search for general information about college, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
256
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(271 citation statements)
references
References 35 publications
7
256
0
8
Order By: Relevance
“…In a similar research carried out by Mazzarol and Soutar (2002), recommendations and considerations from family and friends were highly influential on students' decision. This is in line with the studies by Hossler et al (1999), Cabrera and La Nasa (2000) and Kim and Schneider (2005). There are many instances when family and friends add prospective students to university social media groups or recommend following the university social media groups to interact with professors or administration assistance for course selection (Bodycott, 2009;Lee and Morrish, 2011).…”
Section: Personal Factorssupporting
confidence: 77%
“…In a similar research carried out by Mazzarol and Soutar (2002), recommendations and considerations from family and friends were highly influential on students' decision. This is in line with the studies by Hossler et al (1999), Cabrera and La Nasa (2000) and Kim and Schneider (2005). There are many instances when family and friends add prospective students to university social media groups or recommend following the university social media groups to interact with professors or administration assistance for course selection (Bodycott, 2009;Lee and Morrish, 2011).…”
Section: Personal Factorssupporting
confidence: 77%
“…Economic factors expected to influence college choice include socio-economic status, price, return on investment, and the consumption value of college. Comprehensive reviews of college choice models can be found in Cabrera and La Nasa (2000), Hossler, Braxton, and Coopersmith (1989), Paulsen (1990), and Perna (2006).…”
Section: Introductionmentioning
confidence: 99%
“…More complex models of college choice hypothesize a multi-stage decision making process for potential students where potential students develop aspirations for higher education in the first stage, identify a set of institutions to apply to in the second stage, and choose the institution to attend in the final stage (Cabrera & La Nasa, 2000;Hossler, Braxton, & Coopersmith, 1989;Hossler & Gallagher, 1987;Paulsen, 1990;Perna, 2006). A handful of multiple stage empirical models show that price responsiveness measures may be understated when an analysis exclusively focuses on the enrollment stage because price can also affect aspirations and application decisions (Abraham & Clark, 2006;Curs & Singell, 2002;DesJardins, Ahlburg, & McCall, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers argue that middle school is a critical period for interventions aimed at raising educational aspirations for college-by late high school, it becomes difficult or impossible to accelerate low-achieving students to the necessary levels of college readiness (Cabrera & La Nasa, 2000;Hossler, Schmit, & Vesper, 1999;Shiu et al, 2009). Latino students in particular are more likely to earn a 4-year degree if they plan for it while in middle school, take at least 3 years of high school mathematics, and initially enroll at a 4-year institution instead of a 2-year institution (Cabrera & Bibo, 2010).…”
Section: Academic Planningmentioning
confidence: 99%